Enhancing Education Quality through School-Based Management System and Independenc - Suban, Alwan; Nursita, Lisa; ., Ilham (JURNAL AL-TANZIM, 2024)
This research aims to explore school-based management systems to improve the quality of education through school independence. This research uses a qualitative approach in the form of qualitative descriptive research; the objects of this research are the head of the Madrasah, the school committee, class teachers, one community figure, and two parents (stakeholders). The results of the research show that the successful implementation of school-based management at MTsN 1 Makassar City has been carried out by the work program planned and prepared by the Madrasah so that it can be seen from the orientation towards the effectiveness of the learning process reflected in the teacher's appreciation of curriculum development and its implications, teacher creativity in application. Learning models and learning technology and through school independence. The findings of this research also have implications for the relevance of the school-based management model in the educational context in Indonesia, especially in the madrasa environment. The success of MTsN 1 Makassar City in implementing this model can be an inspiration and example for other madrasas to improve the quality of education and school management.